2021
DOI: 10.1111/bjh.17284
|View full text |Cite
|
Sign up to set email alerts
|

Deferasirox induces cyclin D1 degradation and apoptosis in mantle cell lymphoma in a reactive oxygen species‐ and GSK3β‐dependent mechanism

Abstract: Summary Mantle cell lymphoma (MCL) is a difficult‐to‐treat B‐cell malignancy characterized by cyclin D1 (CD1) overexpression. Targeting CD1 in MCL has been shown to be of therapeutic significance. However, treatment of MCL remains challenging since patients are still subject to early and frequent relapse of the disease. To ensure their high proliferation rate, tumour cells have increased iron needs, making them more susceptible to iron deprivation. Indeed, several iron chelators proved to be effective anti‐can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 53 publications
(93 reference statements)
0
2
0
Order By: Relevance
“…30 Studies have previously demonstrated that iron deficiency inhibited PI3K-Akt signaling, while iron supplementation stimulated cell proliferation by activating PI3K/Akt signaling in different cells. 31,32 Iron supplementation increased Akt phosphorylation, while administration of the PI3K inhibitor completely blocked the iron-induced phosphorylation of Akt. 33 In the current study, maternal FeSuc supplementation was able to regulate PI3K activity by promoting the transcription of growth factors in the placenta.…”
Section: Papermentioning
confidence: 98%
“…30 Studies have previously demonstrated that iron deficiency inhibited PI3K-Akt signaling, while iron supplementation stimulated cell proliferation by activating PI3K/Akt signaling in different cells. 31,32 Iron supplementation increased Akt phosphorylation, while administration of the PI3K inhibitor completely blocked the iron-induced phosphorylation of Akt. 33 In the current study, maternal FeSuc supplementation was able to regulate PI3K activity by promoting the transcription of growth factors in the placenta.…”
Section: Papermentioning
confidence: 98%
“…Chelating agent: Smara et al. ( 50 ) applied iron chelator deferasirox (DFX) to mantle cell lymphoma (MCL) cells, and found that DFX lead to cyclin D1 proteolysis and degradation in a mechanism that requires its phosphorylation on T286 by glycogen synthase kinase-3β (GSK3β). Several iron chelators were proved to be effective anti-cancer agents and potential therapeutic potions, leading to the ubiquitin-proteasome degradation of cyclin D1.…”
Section: The Degradation Of Cyclin D1 Elicits G0/g1 Cell Cycle Arrestmentioning
confidence: 99%
“…The authors also found that the orally administered iron chelator deferasirox [ 4 ] has a synergistic effect with rituximab in killing RRCL cells [ 5 ]. This suggests that activation of p38 MAPK may be a key driver of rituximab resistance and that inhibiting p38 MAPK with deferasirox may be a promising approach to re-sensitizing DLBL cells to rituximab.…”
mentioning
confidence: 99%